Global assessment of production benefits and risk reduction in agroforestry during extreme weather events under climate change scenarios - Dobhal, Sneha; Kumar, Raj; Bhardwaj, Ajay Kumar; Chavan, Sangram Bhanudas; Uthappa, A. R.; Kumar, Manish; Singh, Awtar; Jinger, Dinesh; Rawat, Pravin; Handa, Arun K.; Ramawat, Naleeni (Frontiers in Forests and Global Change, 2024)
Climate change, especially extreme weather events, is threatening agricultural production worldwide. The anticipated increase in atmospheric temperature may reduce the potential yield of cultivated crops. Agroforestry is regarded as a climate-resilient system that is not only profitable, sustainable, and adaptable; but also has strong potential to sequester atmospheric carbon. Agroforestry practices enhance the resilience of agro-ecosystems against adverse weather conditions via moderating extreme temperature fluctuations, provisioning buffers during heavy rainfall, mitigating drought periods, and safeguarding land resources from cyclones and tsunamis-type events. Therefore, it was essential to comprehensively analyze and discuss the role of agroforestry in providing resilience during extreme weather situations. It was hypothesized that integrating trees in the agro-ecosystems could increase the resilience of crops against extreme weather events. The available literature showed that the over-storey tree shade moderates severe temperature (2-4°C) effects on understory crops, particularly in the wheat and coffee-based agroforestry as well as in the forage and livestock-based silvipasture. Further, studies have shown that intense rainstorms can harm agricultural production (40-70%) and cause waterlogging. The farmlands with agroforestry have been reported to be more resilient to heavy rainfall; because of the decrease in runoff (20-50 %) and increase in soil water infiltration. Studies have also suggested that the drought-induced low rainfall damages many crops, but integrating trees can improve microclimate and maintain crop yield by providing shade and windshields, and soil moisture. The meta-analysis revealed that tree shelterbelts could mitigate the effects of high water and wind speeds associated with cyclones and tsunamis by creating a vegetation bio-shield along the coastlines. In general, existing literature indicates that implementing and designing agroforestry practices increases resilience of crops to extreme weather conditions; leading to increase in crop yield by 5-15%. Moreover, the systematic documentation of agroforestry advantages, despite its widely recognized advantages in terms of resilience to extreme weather, is currently insufficient on global scale. Consequently, we provide a synthesis of existing data and its analysis in order to draw reasonable conclusions that can aid in the development of suitable strategies to achieve the worldwide goal of adapting to and mitigating the adverse impacts of climate change.